Potential of temperature-response collagen-genipin sols as a novel submucosal injection material for endoscopic resection - Takatori, Yusaku; Uraoka, Toshio; Narita, Takefumi; Yunoki, Shunji; Yahagi, Naohisa (Endoscopy International Open, 2019)
Background and study aims We developed a novel submucosal (SM) injection material that contained pepsin-solubilized collagen (PSC), genipin (Ge) and phosphate buffer (PB). The aim of this study was to validate safety and usability of it for endoscopic resection (ER). Materials and methods In preliminary studies, 1) appropriate warming time and concentration of Ge, and concentration of NaCl in PB, 2) storage modulus of PSC, Ge, and PB mixture (PSC/Ge), and PSC as a mechanical property, 3) histological finding after injection, and histological toxicity of PSC/Ge was evaluated. We injected PSC/Ge, PSC, sodium hyaluronate (SH), dextrose (DW), and normal saline (NS) into SM of resected porcine stomach. We compared mean height of mucosal elevation after immediate injection (MH) and mean retaining rate at 60 minutes (MR) as ex vivo study. Results Optimal condition of PSC/Ge was Ge 5.5 mMol with 24 hours worming time and NaCl 280 mMol. PSC/Ge had better mechanical property than PSC. It was efficiently integrated and confined to the SM with acceptable toxicity. MH of PSC/Ge (5.1 ± 0.74 mm) and PSC (4.8 ± 0.84 mm) were significantly higher than NS (3.2 ± 0.84 mm). MR of PSC/Ge (100 ± 0.0%) was significantly higher than NS (61.7 ± 11.2%), DW (58.3 ± 11.8%) and SH (61.8 ± 8.6%). Conclusion PSC/Ge and PSC has potential to be safe and usable for ER. PSC/Ge was better than PSC because of better mechanical property than PSC.